Plasmapheresis in neurological disorders: six years experience from University Clinical center Tuzla [version 1; referees: 2 approved] - Osman Sinanović; Sanela Zukić; Adnan Burina; Nermina Pirić; Renata Hodžić; Mirza Atić; Mirna Alečković-Halilović; Enisa Mešić (F1000Research, 2017)
Background: Therapeutic plasma exchange (TPE) is an extracorporeal blood purification technique that is designed to remove substances with a large molecular weight. The TPE procedure includes removal of antibodies, alloantibodies, immune complexes, monoclonal protein, toxins or cytokines, and involves the replenishment of a specific plasma factor. The aim of the study was to describe the clinical response to TPE in various neurological patients, and to assess the clinical response to this therapy. Methods: The study was retrospective. We analyzed the medical records of 77 patients who were treated at the Department of Neurology, University Clinical Center (UCC) Tuzla from 2011 to 2016.   Results: 83 therapeutic plasma exchanges were performed in the 77 patients. There was a slight predominance of male patients (54.5%), with an average age of 51±15.9 years. The most common underlying neurological diseases were Guillain–Barré syndrome (GBS) (37.7%), then chronic inflammatory demyelinating polyneuropathy (CIDP) (23.4%), multiple sclerosis (MS) (11.7%) and myasthenia gravis (10.4%). Less frequent neurological diseases that were encountered were paraneoplastic polyneuropathies (5.2%), neuromyelitis optica (also known as Devic’s disease) (3.9%), motor neuron disease (3.9%), polymyositis (2.6%) and multifocal motor neuropathy (1.2%). Conclusions: Six years experience of therapeutic plasma exchange in neurological patients in our department have shown that, following evidence-based guidelines for plasmapheresis, the procedure was most effective in patients with GBS, CIDP and myasthenia gravis.